2019
DOI: 10.1016/j.vpoa.2018.100001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of faecal diagnostics for detection and predictive modelling of endemic Fasciola hepatica infection in sheep and cattle on Australian farms

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Fecal eggs counts (FEC) are only useful to detect patent infections and have poor sensitivity with low burden infections [ 100 ]. Enzyme-linked immunosorbent assays (ELISAs) such as the coproantigen-ELISAs offer an alternative method of diagnosis from FEC, but they are limited in detecting infection inside the pre-patent period [ 101 , 102 ]. Of the methods mentioned in Table 2, only serological ELISAs were proven to detect specific anti- F. hepatica antibodies as early as ~3 weeks post-infection [ 103 , 104 ]; however, this method cannot distinguish between new and historic infections.…”
Section: Pathogenicity Of Fasciola Spp In Their Definitive Hostsmentioning
confidence: 99%
“…Fecal eggs counts (FEC) are only useful to detect patent infections and have poor sensitivity with low burden infections [ 100 ]. Enzyme-linked immunosorbent assays (ELISAs) such as the coproantigen-ELISAs offer an alternative method of diagnosis from FEC, but they are limited in detecting infection inside the pre-patent period [ 101 , 102 ]. Of the methods mentioned in Table 2, only serological ELISAs were proven to detect specific anti- F. hepatica antibodies as early as ~3 weeks post-infection [ 103 , 104 ]; however, this method cannot distinguish between new and historic infections.…”
Section: Pathogenicity Of Fasciola Spp In Their Definitive Hostsmentioning
confidence: 99%
“…Th e fascioliasis can be diagnosed using the classical methods of helminthological dissection (Skrjabin, 1928) scatological methods (Esteban et al, 1998;Cringoli et al, 2010;2017;Al-Mamunet al, 2011;Carneiro et al, 2018;Zárate-Rendón et al, 2019), and enzyme-linked immunosorbent test systems, ELISA (Hillyer, 1999;Akca et al, 2014;Munita et al, 2019). It has been shown that both scatological and ELISA have similar resolution (George et al, 2019), which makes the previously obtained results comparable and allows for eff ective control of the prevalence of fascioliasis. Information on the prevalence of fascioliasis among diff erent host species is highly controversial.…”
Section: Introductionmentioning
confidence: 97%
“…For diagnosis, the farm history and epidemiology data might be followed to suggest the fluke risk; however, traditional examination of slaughtered animals remains the most definitive indicator. Also, identification of fluke eggs in fecal samples of clinically suspected animals is useful; however, it's time-consuming, laborious and lack of sensitivity, particularly, in animals having low parasitic burdens [9,10]. In last decade, serological assays such as enzyme-linked immunosorbent assay (ELISA) offers a rapid, valuable and sensitive tool for indication of infection based on positive reaction of anti-fluke antibodies in blood samples [11].…”
Section: Introductionmentioning
confidence: 99%